Delayed diagnosis of right-sided Bochdalek hernia in an infant: A case report - Majd Oweidat; Mosaikah Anati; Mohammed Aldwaik; Haya Tariq Mohammed Taha (Journal of Pediatric Surgery Case Reports)
Introduction: Congenital diaphragmatic hernia (CDH) is a rare developmental anomaly characterized by an abnormal diaphragmatic opening that allows abdominal organs to herniate into the thoracic cavity. CDH is typically diagnosed before or shortly after birth. Delayed presentations are uncommon and may lead to misdiagnosis. Case presentation: An 11-month-old female, born full-term via spontaneous vaginal delivery, presented with a three-day history of mild intermittent dry cough and nasal congestion. The prenatal history was unremarkable, and a no antenatal ultrasound had been done. She had a history of recurrent respiratory symptoms, frequently diagnosed as respiratory infections. She had never undergone chest imaging. On examination, diminished air entry on the right chest was noted, prompting imaging. Chest x-ray showed multiple radiolucent areas in the lower half of the right hemithorax. Computerized tomography (CT) scan showed a right-sided congenital diaphragmatic hernia with bowel loops herniating into the right hemithorax. The patient was taken to the operating room for the repair of the CDH. We did transverse supra-umbilical laparotomy. Intraoperative findings confirmed the herniation of small bowel and the transverse colon through a right posterior diaphragmatic defect, or Bochdalek-type CDH, with normal diaphragmatic crura. We repaired the CDH primarily without the need for a prosthetic mesh. She received postoperative care in the pediatric intensive care unit and recovered without complications. At one week and at one month of follow up, she was gaining weight appropriately, had no respiratory distress, and had no hernia recurrence. Conclusion: Infants with recurrent respiratory symptoms should undergo a chest x-ray to rule out a late-presenting CDH.